Microstructure and Texture Evolution of Friction-Stir-Welded AA5052 and AA6061 Aluminum Alloys - Luqman Hakim, Ahmad Shah; Shamsolhodaei, Amirali; Walbridge, Scott S.; Gerlich, Adrian (MDPI AG, 2026)
This study examines the through-thickness microstructure and crystallographic texture evolution in friction-stir-welded (FSWed) AA5052-H32 and AA6061-T651 aluminum alloys using a tri-flats threaded pin tool. Optical microscopy and electron backscatter diffraction (EBSD) were employed to characterize grain morphology, boundary misorientation, and texture components across the weld thickness. Both alloys exhibited progressive grain refinement and increased high-angle grain boundary fractions from the top to the bottom of the stir zone due to combined thermal and strain gradients. The FSWed AA5052 displayed dominant {111}<110> and Y + γ fiber components at the upper and mid regions, whereas AA6061 showed more randomized textures. At the bottom region, both alloys developed rotated Goss {011}<01-1> and weak A ({112}<110>) and α fiber components. These results clarify how alloy strengthening mechanisms—solid-solution versus precipitation hardening—govern texture evolution under different strain-path and heat input conditions. The findings contribute to optimizing process parameters and material selection for structural-scale FSW aluminum joints in industrial applications such as bridge decks, transportation panels, and marine structures.